Researching and analyzing the features of oil and demand for transporting oil derivates in the area of Belgrade - Jovanović, Vojkan D.; Tica, Slaven; Milovanović, Branko; Živanović, Predrag (Transport, 2009)
The paper contains a summary of results obtained when researching demand for transporting dangerous goods of class 3 (oil and oil derivates) in the area of the city of Belgrade in 2007. Considering all transport modes used for carrying oil and oil derivates (road, rail and water transport), we present the total quantities of transported goods on a percentage basis. In light of road transport, the paper presents the features of demand for transport in terms of time and space that are a basis for the management of transporting dangerous goods and input to defining transportation routes to dangerous goods. Among the features of demand for transport in terms of time, the paper presents the quantities of goods transported within different months of the year, different week days and different periods of the day. The features of demand for transport in terms of space presented in the paper are goods flow features depending on their origin and the destination of movement in relation to the defined serviced area and the load of traffic network with goods flows. First published online: 27 Oct 2010